Electronic smart textiles: new possibilities in textile industry in Bangladesh - Омар Фарук; Сайма Махаджабин; Нараян Чандра Натх; Прианка Кабирадж (Современные инновации, системы и технологии)
Manufacturing has made significant advances this century across all technical and technological domains. In the race for this kind of growing, textiles compete. An interesting development in the textile and apparel sectors is smart textiles. Intelligent textiles are capable of sensing, processing, and interpreting a wide range of impulses and reactions, whether they come from electrical, chemical, biological, magnetic, or other sources. Three categories may be used to categorize the amount of intelligence: bright materials, dynamic creative clothes, and passively intelligent clothing. The five unique operations of innovative textiles are devices, retention, networking, data processing, and detectors. But it must be uniform for all garment functions involving robustness, use, and resistance to conventional textile maintenance methods. It is no longer limited to our ideas or just evident in Hollywood productions; it now has great potential and is part of our daily lives. These days, it is widely used in many different areas, such as emergency clothing, spy clothing, army clothing, and health and security gear. In addition, biological applications, athletic apparel, safety equipment, textiles, rocketry, and a host of other things. Thus, another name for it might be next-generation apparel. This study aims to give a broad overview of intelligent textiles, including their many types and functions. An inventory of smart clothing items, as well as contemporary intelligent textile goods and applications, are all examined.